A Case of Fulminant Hepatic Failure with Neonatal Cholestasis Caused by Disseminated Herpes Simplex Virus (HSV) Infection (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Disseminated herpes simplex virus infection is an life threatening infection which may initially present as cholestasis, but eventually lead to multiple organ failure with a high mortality rate. But the good news is that the introduction of antiviral agent like acyclovir for the treatment of neonatal herpes has significantly improved the outcome of this potentially devastating infection. The early initiation of acyclovir highly depends on clinician’s suspicion, especially when overt signs of the infection are absent. So the objective of our case report was to raise awareness among the physicians to consider herpes virus infection in the differential when a patient present with features of cholestasis and hepatic failure. Case Presentation: Our case is aone month old male infant who got admitted in Chittagong Medical Hospital on 7th January, 2023 with the complaints of lethargy, blood mixed vomiting and black stool for 1 day with a history of jaundice and pale stool from 3rd week of life. His bleeding manifestations exacerbated and developed features of hepatic failure with coagulopathy. He was treated with plasma transfusion, viamin k, injectable antibiotics and other supportive care. A TORCH panel was sent. HSV Ig G came positive with 12 folds increased titre. Observing his deteriorating consciousness level intravenous acyclovir 60 mg/kg/day was initiated on 16th January, 2023. Within 3-4 days his overall general condition improved. The baby was discharged after getting 21 days of acyclovir therapy. Conclusion: Neonatal herpes virus infection can be a life threatening condition. An early diagnosis and effective treatment with antiviral agent can reduce morbidity and mortality.Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 99-103